Autoimmune Blistering Disease in Children - Hazlianda, Cut Putri; Siahaan, Ade Gustina (Journal of Society Medicine, 2023)
The skin is a particular organ that shields the body from physical stress and other external stresses. There are three layers of skin: epidermis, dermis, and subcutis. The three layers act as interrelated units in carrying out the above functions. One of the skin diseases that can be found is an autoimmune blister or bullous disease that can affect children. Autoimmune bullous or blisters are rare in children, but their quality of life is compromised if they suffer from this disease. Included in autoimmune bullous diseases in children are Linear Immunoglobulin A Bullous Dermatosis (LABD), Dermatitis Herpetiformis (DH), Pemphigus Vulgaris (PV), Pemphigus Foliaceus (PF), Paraneoplastic Pemphigus (PNP), Bullous Pemphigoid (BP), Mucous Membrane (cicatricial) Pemphigoid (MMP), Epidermolysis Bullosa Acquisita (EBA). Diagnosing and treating patients with autoimmune bullous diseases is challenging for clinicians. The skin of infants and children is anatomically thinner than adults, so they are more prone to develop bullae when traumatized.